TO STUDY PRESCRIPTION PATTERN IN THE MANAGEMENT OF OSTEOARTHRITIS IN TERTIARY CARE HOSPITAL - LAHAMATE, SHRIKANT B; U RAZVI, SYED (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The leading cause of disability is arthritis among adults worldwide. Osteoarthritis (OA) is the most common form of joint disease and the leading cause of pain in elderly people. The aim of the study was to study the prescription pattern in the management of OA. Methods: A prospective observational study was conducted in a tertiary care hospital for period of 12 months in collaboration with the department of orthopedics. A total of 630 patients enrolled in the present study with fulfilling inclusion and exclusion criteria. Patients’ data recorded in case report form and analyzed to study the prescription pattern. Results: A total of 630 cases were enrolled in this study. Osteoarthritis is more common in female i.e. 55% followed by male i.e. 45% of patients. Old age (39.84%) is most common risk factor followed by obesity (29.68%) in OA patient. Most commonly prescribed drug was diclofenac followed by paracetamol. Nonsteroidal anti-inflammatory drugs were most commonly prescribed class of drug, i.e., 92.19%. In this study, combination therapy most commonly prescribed, i.e., 75.4% followed by monotherapy, i.e., 24.6%. Combination therapy in OA patients two drug therapy, i.e., 88.42% followed by three drug therapy, i.e., 10.53%. Conclusions: The principal aim of drug utilization research is to facilitate the rational use of drugs. The study shows that OA more common in female patient than male patient. The most common disease distribution site was knee in OA patient. Old age was the most common encounter risk factor in OA patient. Combination therapy was most commonly used than single drug therapy.